(untitled) (Journal of the College of Education for Women, 2019)
AbstractThe study aims to recognize the degree of consumptions awareness of theIraqi family; the conscious and studied planning of the family; budget and theobject study of the rationalization s consumption.The research study 100 specimens of both students and employees whoare housewives at the department of home economics of the college ofEducation for women.Questioner the items are 22.One of the most important results that the study finds is the availability ofconsumption’s awareness’s level particularly of low income families andcollege degrees hdders who are over 35.The study recommends the necessity of a conscious and studiedplanning of the family’s budget; its purchase and consumption of clothes aswell as the importance of focusing on the quality.